Nanoparticle Contrast-enhanced T1-Mapping Enables Estimation of Placental Fractional Blood Volume in a Pregnant Mouse Model - Badachhape, Andrew A. (Sci Rep, 2019)
Non-invasive methods for estimating placental fractional blood volume (FBV) are of great interest for characterization of vascular perfusion in placentae during pregnancy to identify placental insufficiency that may be indicative of local ischemia or fetal growth restriction (FGR). Nanoparticle contrast-enhanced magnetic resonance imaging (CE-MRI) may enable direct placental FBV estimation and may provide a reliable, 3D alternative to assess maternal-side placental perfusion. In this pre-clinical study, we investigated if placental FBV at 14, 16, and 18 days of gestation could be estimated through contrast-enhanced MRI using a long circulating blood-pool liposomal gadolinium contrast agent that does not penetrate the placental barrier. Placental FBV estimates of 0.47 ± 0.06 (E14.5), 0.50 ± 0.04 (E16.5), and 0.52 ± 0.04 (E18.5) were found through fitting pre-contrast and post-contrast T1 values in placental tissue using a variable flip angle method. MRI-derived placental FBV was validated against nanoparticle contrast-enhanced computed tomography (CE-CT) derived placental FBV, where signal is directly proportional to the concentration of iodine contrast agent. The results demonstrate successful estimation of the placental FBV, with values statistically indistinguishable from the CT derived values.